OPTIMASI POSISI PILOT MENGGUNAKAN ALGORITMA GENETIKA UNTUK MENINGKATKAN KINERJA Wi-Fi 802.11n - Wahyul Amien Syafei; Yunda Kumala Nasution; Sukiswo Sukiswo (Diponegoro University, 2013)
Wi-Fi is wireless communication technology that used widely not only for accessing the internet but also communicating data, image, voice and video. The newest wi-fi technology is 802.11n as an extention of 802.11a/b/g. By combining OFDM and MIMO techniques it can provide throughput up to 600Mbps. One of important factors to achieve such high throughput is the pilot position in training sequence. Wi-fi802.11n allocates it’s pilots orthogonally. This research optimizes the pilot location using Genetic Algorithm Differential Evolution. Optimum pilot position improves the accuracy of synchronization which leads to enhance the performance. The invented optimum pilot position set then be implemented into wi-fi 802.11n simulator to be analyzed the performance enhancement which represented in grafic BER vs SNR curve.Run test under channel model B and D proof that the invented optimum pilot position gives performance enhancement of 0,5 dB and maintain it’s stability compared towi-fi 802.11n system with set ortogonal pilot position.